BRIDGING THE GAP: A QUALITATIVE ANALYSIS OF GENDERED PERCEPTIONS ON GOOD AND EFFECTIVE ENGLISH TEACHER - Dewi, Kadek Ayu Komala; Artini, Luh Putu; Wahyuni, Luh Gede Eka (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2024)
This study endeavors to delve into the nuanced perceptions of male and female students regarding the attributes of a good and effective English teacher, employing a descriptive qualitative research design. Conducted at SMA Negeri 1 Tabanan, the research engaged three class representatives encompassing a total of 108 students. Through an open-ended questionnaire featuring 10 statements each on the qualities of a good and effective English teacher, a rich dataset emerged from the insights of 85 participants (55 females and 30 males), meticulously collected via a streamlined Google Form. The intriguing findings unveiled a distinctive trend among female students, who showcased a penchant for the emotional facets of teaching, placing a premium on qualities such as empathy, understanding, and sensitivity when conceptualizing an exemplary teacher. In contrast, their male counterparts demonstrated a pragmatic stance, valuing a teacher's keen awareness of their competency level. A unanimous agreement from both genders emerged, highlighting the pivotal role of a flexible and adaptable teaching approach for an English teacher's effectiveness, ensuring adept navigation of unforeseen challenges and the cultivation of a thriving learning environment for all students